A Photochromic Azobenzene Peptidomimetic of a β-Turn Model Peptide Structure as a Conformational Switch - Nuti, Francesca; Gellini, Cristina; Larregola, Maud; Squillantini, Lorenzo; Chelli, Riccardo; Salvi, Pier Remigio; Lequin, Olivier; Pietraperzia, Giangaetano; Papini, Anna Maria (Frontiers in Chemistry, 2019)
The insertion of azobenzene moiety in complex molecular protein or peptide systems can lead to molecular switches to be used to determine kinetics of folding/unfolding properties of secondary structures, such as -helix, -turn or -hairpin. In fact, in azobenzene, absorption of light induces a reversible trans ↔ cis isomerization, which in turns generates a strain or a structure relaxation in the chain that causes peptide folding/unfolding. In particular azobenzene may permit reversible conformational control of hairpin formation. In the present work a synthetic photochromic azobenzene amino acid derivative was incorporated as a turn element to modify the synthetic peptide [Pro7,Asn8,Thr10]CSF114 previously designed to fold as a type I -turn structure in biomimetic aqueous solution. In particular, the P-N-H fragment at positions 7-9, involved in a -hairpin, was replaced by an azobenzene amino acid derivative (synthesized ad hoc) to investigate if the electronic properties of the novel peptidomimetic analogue could induce variations in the isomerization process. The absorption spectra of the azopeptidomimetic analogue of the type I -turn structure and of the azobenzene amino acid as control were measured as a function of the irradiation time exciting into the respective first * and n* transition bands. Isomerization of the azopeptidomimetic results strongly favoured by exciting into the * transition. Moreover, conformational changes induced by the cis↔ trans azopeptidomimetic switch were investigated by NMR in different solvents.